Simple Bouquet Homemade: Creative Business Innovation for Economic Enrichment of the Community in the Blora Randublatung Cursed Village - Munir, Akhmad Sirojudin; Luthfi Hidayah; Suci Yongki Setiowati; Nurul Mustafidah (Jurnal Insan Pengabdian Indonesia, 2024)
The program "Simple Bouquet Homemade: Creative Business Innovation for Economic Empowerment of the People in the Blora Cursed Village" aims to improve the well-being of the people through simple bouquet making training that can be run as a creative undertaking. The program involved 30 participants from household mothers and village youths, who previously had no skills in the area of florist. The results of the program showed an improvement in the skills of participants in bouquet making, which was followed by an increase in household income by up to 20-30% after they started a business. In addition, the establishment of small business groups has successfully encouraged collaboration and economic independence among the participants. Nonetheless, some challenges such as access to raw materials and the constraints of online marketing technology need further attention. The programme successfully demonstrates that innovation in creative business can be an effective solution for empowering the economy of rural communities, and can be replicated in other areas with appropriate adjustments.